Massage manual : step-by-step techniques for a complete body treatment - Harrold, Fiona (Connections Book Pub. LondonGB, 1997)
Provides step-by-step instructions for practising and perfecting massage skills, both for self- and other-massage, and illustrates each routine with clearly defined photographs. Outlines common medical conditions including: abdominal bloatedness; calf cramps, constipation, and swollen ankles, for which massage may be therapeutic. Describes 10 essential oils needed for the procedures.